SEDIMENTARY ROCKS AT MERIDIANI PLANUM: ORIGIN, DIAGENESIS, AND IMPLICATIONS FOR LIFE ON MARS - Squyres S.W.; Knoll A.H. (My University, 2005)
The MER rover Opportunity has carried out the first outcrop-scale investigation of ancient sedimentary rocks on Mars. The rocks, exposed in craters and along fissures in Meridiani Planum, are sandstones formed via the erosion and re-deposition of fine grained siliciclastics and evaporites derived from the chemical weathering of olivine basalts by acidic waters. A stratigraphic section more than seven meters thick measured in Endurance crater is dominated by eolian dune and sand sheet facies; the uppermost half meter, however, exhibits festoon cross lamination at a length scale that indicates subaqueous deposition, likely in a playa-like interdune setting. Silicates and sulfate minerals dominate outcrop geochemistry, but hematite and Fe3D3 (another ferric iron phase) make up as much as 11% of the rocks by weight. Jarosite in the outcrop matrix indicates precipitation at low pH. Cements, hematitic concretions, and crystal molds attest to a complex history of early diagenesis, mediated by ambient ground waters. The depositional and early diagenetic paleoenvironment at Meridiani was arid, acidic, and oxidizing, a characterization that places strong constraints on astrobiologial inference.